Chromosomal Mutagenesis - Pruett-Miller, Shondra M. (Methods in Molecular Biology, Methods and Protocols, 2015)
This new edition explores current and emerging mutagenesis methods focusing specifically on mammalian systems and commonly used model organisms through comprehensive coverage and detailed protocols. Since the first edition, major advances and discoveries have made chromosomal mutagenesis a widely used technique and one that is available to any molecular biology laboratory, and this collection provides detailed protocols, case-studies, and reviews from thought-leaders in the field. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and fully updated, Chromosomal Mutagenesis, Second Edition aims to help speed scientific discovery and aid in the next advances in the field